IMPROVING COMMUNITY AWARENESS OF THE HEALTH BENEFITS OF OYSTER MUSHROOMS THROUGH FUNCTIONAL FOOD EDUCATION AMONG THE SIPIN DANAU SEJAHTERA WOMEN'S FARMER GROUP - Kasmadi, Fathnur Sani; Yuliawati, Yuliawati; Maritsa, Hasna Ul (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2026)
Oyster mushrooms (Pleurotus ostreatus) are functional foods rich in nutrients and bioactive compounds that provide various health benefits. However, community awareness of these benefits remains limited. This community service program aimed to improve awareness of the health benefits of oyster mushrooms through functional food education among members of the Sipin Danau Sejahtera Women's Farmer Group. A one-day educational program was implemented using a three-stage approach comprising a baseline assessment through a pre-test, interactive education on the nutritional composition and health benefits of oyster mushrooms, and program evaluation using a questionnaire. A total of 32 participants attended the program. The educational intervention effectively increased participants' knowledge, with the mean knowledge score improving from 65.4% before the intervention to 98.3% after the educational session. Participants also demonstrated a better understanding of oyster mushrooms as functional foods that support healthy dietary practices. Functional food education effectively enhanced community awareness of the health benefits of oyster mushrooms. This educational approach has the potential to promote healthier dietary behaviors and increase the utilization of locally available functional foods to support community health. Keywords: community service; functional food; health; pleurotus ostreatus